The genus Polycope (Polycopidae, Ostracoda) in the North Atlantic and Arctic: taxonomy, distribution, and ecology. Issue 2 (3rd March 2016) - Karanovic, Ivana; Brandão, Simone N.
Abstract : With almost 200 species described from all over the world, Polycope Sars, 1866 is the most specious and eurytopic genus of the exclusively marine family Polycopidae. Unlike other members of the subclass Myodocopa, polycopids are commonly found in fossiliferous rocks from strata as old as the Carboniferous, which makes them a useful tool in palaeoenvironmental reconstructions. The genus Polycope in particular is an opportunistic group and can putatively serve as an indicator of organic rich, fine grained sediment, reduced sea ice, and increased productivity, which is especially important when correlating biological data with the Quaternary climate changes that often requires accurate generic and species identifications. Polycopid taxonomy is relatively complicated because species tend to have conservative shell shapes and the soft body is extremely reduced, which can lead to numerous misidentifications, especially when fossil and Subrecent taxa are mixed and the shell is the only available source of taxonomic information. Here we study Polycope species collected during the first cruise of the IceAge project from the margin off Iceland. In total, four species have been recovered from 200 to 2747 m depth. They have been identified as P. pseudoinornata Chavtur, 1983, P. punctata Sars, 1869, P. yasuharai sp. nov., and P. sp. This is the first time since the middle of the 19th century that members of this genus have been studied in the North Atlantic and Arctic using both their soft parts and shells. It allowed us to reconsider numerous previous records of Polycope from this region. Beside a critical overview of the polycopid diversity in the North Atlantic and Arctic, and detailed taxonomic (re)descriptions of the newly collected specimens, we also provide maps of their distributions, analyse their ecological preferences, and offer a preliminary phylogeny of the North Atlantic species of Polycope based on 28S rDNA sequences. http://zoobank.org/urn:lsid:zoobank.org:pub:17EB9011-1715-4C1A-A854-FD0770F36E76